2012
DOI: 10.1024/0301-1526/a000188
|View full text |Cite
|
Sign up to set email alerts
|

Use of biosynthetic prosthesis (Omniflow II®) to replace infected infrainguinal prosthetic grafts - first results

Abstract: In the absence of appropriate autologous material biosynthetic grafts seem to be a possible alternative to replace infected infrainguinal grafts. The different mechanical properties of biosynthetic grafts may be of certain disadvantage in infragenicular reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 5 publications
0
20
0
1
Order By: Relevance
“…If associated with the anastomosis, the graft should be removed and the native vessels repaired. If the infected aneurysm is localized and in the mid graft, some authors have suggested excision of the affected area and repair with a biological or biosynthetic graft although this has been described in bypass rather than in VA [ 42 ].…”
Section: Managementmentioning
confidence: 99%
“…If associated with the anastomosis, the graft should be removed and the native vessels repaired. If the infected aneurysm is localized and in the mid graft, some authors have suggested excision of the affected area and repair with a biological or biosynthetic graft although this has been described in bypass rather than in VA [ 42 ].…”
Section: Managementmentioning
confidence: 99%
“…The plan was to remove the femoro-femoral bypass and the femoral-popliteal bypass and replace both with biological Omniflow grafts and repair both aneurysms. This decision is supported by a prospective study in 2012 showing that biological grafts were not reinfected up to 20 months after the operation 21 . However they did report that the mechanical properties of these grafts may be disadvantageous and more prone to kinking and obstruction.…”
Section: Managementmentioning
confidence: 98%
“…Bovinný xenograft je potenciálne viac imunoalergénny ako ľudský allograft. Napriek tomu, že pri použití xenoperikardiálnych a iných xenoimplantátov boli dosiahnuté dobré krátodobé výsledky, 19 zatiaľ chýbajú klinické štúdie, ktoré by dlhodobú úspešnosť použitia týchto preparátov potvrdili.…”
Section: Diskusiaunclassified